ACG Clinical Guideline: Genetic Testing and Management of Hereditary Gastrointestinal Cancer Syndromes. (February 2015) - Syngal, Sapna; Brand, Randall E; Church, James M; Giardiello, Francis M; Hampel, Heather L; Burt, Randall W
Abstract : N/A: This guideline presents recommendations for the management of patients with hereditary gastrointestinal cancer syndromes. The initial assessment is the collection of a family history of cancers and premalignant gastrointestinal conditions and should provide enough information to develop a preliminary determination of the risk of a familial predisposition to cancer. Age at diagnosis and lineage (maternal and/or paternal) should be documented for all diagnoses, especially in first‐ and second‐degree relatives. When indicated, genetic testing for a germline mutation should be done on the most informative candidate(s) identified through the family history evaluation and/or tumor analysis to confirm a diagnosis and allow for predictive testing of at‐risk relatives. Genetic testing should be conducted in the context of pre‐ and post‐test genetic counseling to ensure the patient's informed decision making. Patients who meet clinical criteria for a syndrome as well as those with identified pathogenic germline mutations should receive appropriate surveillance measures in order to minimize their overall risk of developing syndrome‐specific cancers. This guideline specifically discusses genetic testing and management of Lynch syndrome, familial adenomatous polyposis (FAP), attenuated familial adenomatous polyposis (AFAP), MUTYH ‐associated polyposis (MAP), Peutz–Jeghers syndrome, juvenile polyposis syndrome, Cowden syndrome, serrated (hyperplastic) polyposis syndrome, hereditary pancreatic cancer, and hereditary gastric cancer.